2016
DOI: 10.26740/parama.v3i2.1523
|View full text |Cite
|
Sign up to set email alerts
|

Pesan Dari Slebor: Analisis Wacana Kritis Terhadap Fenomena Bahasa Tulis Stiker Sepeda Motor

Abstract: One of the interesting phenomena in the use of written language is found in motor cycle stickers. The use of language is able to reveal social dimension and show social culture of a given society. This study focuses on messages in the motorcycle stickers: 1) describing patterns of language structures and other linguistic elements; 2) describing relationship patterns among participants; and 3) unsealing what and how socio-cultural phenomena. Theoretical Framework in this study refers to what is stated by Faircl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thus, other interpreters seem to participate. (10) The taklim assemblies continue to teach the procedures for ablution, prayer, zakat, fasting, pilgrimage, and other rituals… (Tejo & Nursamad Kamba, p. 62)…”
Section: Representation Of the Synecdoche Totem Pro Parte Sage Used In Languagementioning
confidence: 99%
“…Thus, other interpreters seem to participate. (10) The taklim assemblies continue to teach the procedures for ablution, prayer, zakat, fasting, pilgrimage, and other rituals… (Tejo & Nursamad Kamba, p. 62)…”
Section: Representation Of the Synecdoche Totem Pro Parte Sage Used In Languagementioning
confidence: 99%
“…The finding generally demonstrated the expression of the language on the body truck with semiotic analysis which fixated on the theory and interprets meaning in a specific way that contains aspects of sign, signifier, and signified which exist in the society. The second current study conducted by Setiawan and Halum (2016), indicated the language phenomenon concerning socio-cultural issues found on motorcycle stickers using critical discourse analysis. Besides, this study also focused on the patterns of language structure and other linguistic elements that appear on motorcycle stickers.…”
Section: Introductionmentioning
confidence: 98%